COMERCIALIZACIÓN DE UNA NUEVA BEBIDA PROBIÓTICA DE AGAVE ENTRE LA POBLACIÓN URBANA Y LA PROBLACIÓN RURAL. MÉXICO - Laura Mayela Ramírez Murillo; Alicia Lucrecia Yáñez Moneda (European Scientific Journal, ESJ, 2014)
The Agave juice is a whitish, cloudy liquid that is obtained from the Agave plant, and since pre-Columbian times has been used to produce an alcoholic drink known as pulque. This drink has been consumed in rural areas of Mexico. The urban population, however, has had some degree of rapprochement with pulque due to migration of rural workers to the city. The Agave juice has nutritional properties and amino acids, vitamins and sugars and when added with a probiotic microorganism its nutritional value is further increased. The aim of this study is to analyze the factors causing the purchase and acceptance of a probiotic drink based on agave juice in a rural community of the State of Tlaxcala and an urban area of the State of Puebla. This is a non-experimental, descriptive and simple cross sectional research. The results show that rural consumers are willing to buy the new product based on Agave juice, if its promotion manages to convey its nutritional properties, if its sensory properties are changed and if the product really gives special nutrients to improve the health of the population. While urban consumers do not consider it feasible to be consumed.